Dynamic characteristics of elastically supported beam subjected to a compressive axial force and a moving load - Kien, Nguyen Dinh; Ha, Le Thi (Vietnam Journal of Mechanics, 2011)
This paper discusses the dynamic characteristics of an elastically supported Euler-Bernoulli beam subjected to an initially loaded compressive force and a moving point load. The eccentricity of the axial force is taken into consideration. The time-histories for beam deflection and the dynamic magnification factors are computed by using the Galerkin finite element method and the implicit Newmark method. The effects of decelerated and accelerated motions on the dynamic characteristics are also examined. The influence of the axial force, eccentricity and the moving load parameters on the dynamic characteristics of the beams is investigated and highlighted